Impact of antibiotic-loaded PMMA spacers on the osteogenic potential of hMSCs - Hofmann, Jakob; Bewersdorf, Tim; Sommer, Ulrike; Lingner, Thomas; Findeisen, Sebastian; Schamberger, Christian T.; Schmidmaier, Gerhard; Großner, Tobias (Antibiotics, 2024)
Antibiotic-loaded PMMA bone cement is frequently used in modern trauma and orthopedic surgery. Although many of the antibiotics routinely applied are described to have cytotoxic effects in the literature, clinical experience shows no adverse effects for bone healing. To determine the effects of antibiotic-loaded PMMA spacers on osteogenesis in vitro, we cultivated human bone marrow mesenchymal stem cells (BM-hMSCs) in the presence of PMMA spacers containing Gentamicin, Vancomycin, Gentamicin + Clindamycin as well as Gentamicin + Vancomycin in addition to a blank control (agarose) and PMMA containing no antibiotics. The cell number was assessed with DAPI staining, and the osteogenic potential was evaluated by directly measuring the amount of hydroxyapatite synthesized using radioactive 99mTc-HDP labelling as well as measuring the concentration of calcium and phosphate in the cell culture medium supernatant. The results showed that Gentamicin and Vancomycin as well as their combination show a certain amount of cytotoxicity but no negative effect on osteogenic potential. The combination of Gentamicin and Clindamycin, on the other hand, led to a drastic reduction in both the cell count and the osteogenic potential.